The Dynamics of Beef Industry in Malaysia: A Case Study of Nusantara Meat Berhad - Mohd Hasbi, Jaafar (2023)
This study examines the factors and challenges of the beef industry in Malaysia. This qualitative study uses an in depth interview methodology. Thirteen stakeholder informants were selected, involving beef producers, competitors, customers, and government officials. Based on the literature review, the beef industry faces various challenges and obstacles, such as production, land availability, animal feed costs, labour costs, cattle recruitment, and livestock innovation. In addition to the supply and marketing issues, prices, promotions, competition, government regulations, logistics processing units, finance and exchange rates are also being identified. This study has also discovered obstacles relating to the beef industry’s growth. Unstructured and semi-structured questions were asked of the informants who participated in these in-depth interviews. Information collected from interviews and in-depth observations was analysed through mnemonic writing. The results are organised according to basic, organisational, and global themes. In conclusion, this study summarised a qualitative phenomenon about the beef industry and its contribution to the country’s economic growth. It also suggests future research, implications, and theoretical and practical issues for stakeholders in dealing with the beef industry issues in Malaysia.